EFIKASI DIRI DAN MOTIVASI BERPRESTASI DALAM PEMBELAJARAN BERBASIS ONLINE SELAMA MASA PANDEMI COVID-19 - Nona Dwi Fortuna; Christin Marchela; Berliana Charolina; Sixwanda Febrina; Rina Mirza (UIN Sumatera Utara Medan, 2022)
Throughout the Covid-19 pandemic, many students skilled a decrease in achievement motivation. where they feel much less confident in the abilities they have. This research pursuits to find out the connection between self efficacy and motivation to excel in online based learning at some point of the pandemic in Binjai state high school students. The observe used quantitative techniques, with a sample quantity of 182 students, using proportionate random sampling strategies. data collection uses the self-efficacy scale and the achievement motivation scale. This research data changed into analyzed using regression analysis and determined a positive relationship among self-efficacy and 3.8 percent fulfillment motivation. This shows that self efficacy has a role in increasing the motivation to excel in Binjai state high school students in online based studying in the course of the covid-19 pandemic.